2022
DOI: 10.3390/nu14061275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Fasting on Brain Metabolism

Abstract: We are facing an obesity epidemic, and obesity itself and its close companion, type 2 diabetes, are independent risk factors for neurodegeneration. While most medical treatments fail to induce a clinically meaningful improvement in neurodegenerative disorders, lifestyle interventions have emerged in the spotlight. A recently rediscovered approach is intermittent fasting (IF), which, compared to the classic caloric restriction regimens, limits only the time of eating, rather than the number of calories allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 109 publications
0
15
0
1
Order By: Relevance
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Several authors suggest different mechanisms underlying IFand CR-induced AHN. Both paradigms have been related to an overall increment of the expression of neurotrophins (Elesawy et al, 2021), such as neurotrophin-3 (Park et al, 2008(Park et al, , 2013Pani, 2015), ciliary neurotrophic factor (Park et al, 2008) and BDNF (Park et al, 2008;Treccani et al, 2014;van Praag et al, 2014;Kaptan et al, 2015;Kim et al, 2015;Morgan et al, 2017;Li et al, 2020;Brocchi et al, 2022;Setel et al, 2022) especially in newly generated neurons of the dentate gyrus (Lee et al, 2002;Elesawy et al, 2021). Caloric restricted animals displayed increased expression of genes of neuronal protection and differentiation, such as NeuroD1 (Brandhorst et al, 2015;Li et al, 2020), Notch (Baik et al, 2020), Klotho (Dias et al, 2021), Egr1 (Hornsby et al, 2016).…”
Section: Caloric Restriction and Intermittent Fastingmentioning
confidence: 99%
“…In a cross-sectional study involving 883 older Italian adults, Currenti and colleagues found that individuals adherent to 10-h TRF were less likely to have CI, compared to those with no eating time restrictions 7 . TRF may play a role in the regulation of behavior and modulation of the expression of brain derived neurotrophic factor (BDNF), so as to influence neurogenesis and cognitive function 8 . However, an 8-week pilot clinical trial showed that IF did not change cognitive performance 9 .…”
Section: Introductionmentioning
confidence: 99%